Immunocastration in adult boars as a model for late‐onset hypogonadism. (8th July 2022) - Batorek‐Lukač, Nina; Kress, Kevin; Čandek‐Potokar, Marjeta; Fazarinc, Gregor; Škrlep, Martin; Poklukar, Klavdija; Wesoly, Raffael; Stefanski, Volker; Vrecl, Milka
Abstract: Background: While immunocastration has been studied in male pre‐pubertal pigs, data on older, sexually mature animals are limited. To understand the physiological effects of androgen deprivation in the late sexual development phase, we compared mature immunocastrated boars ( n = 19; average age = 480 days) to young male immunocastrated pigs ( n = 6; average age = 183 days) and young entire males ( n = 6; average age = 186 days) as positive and negative controls, respectively. Objectives: We hypothesized that the timing of gonadotropin‐releasing hormone suppression (early or late sexual development phases) influences the extent of reproductive function inhibition, histological structure of testicular tissue, and expression levels of selected genes related to steroid metabolism. Materials and methods: Antibody titer, hormonal status, and histomorphometric analysis of testicular tissue were subjected to principal component analysis followed by hierarchical clustering to evaluate the immunocastration effectiveness in mature boars. Results: Hierarchical clustering differentiated mature immunocastrated boars clustered with young immunocastrated pigs from those clustered with entire males. Although all mature immunocastrated boars responded to vaccination, as evidenced by the increased gonadotropin‐releasing hormone antibody titers ( p < 0.001), decreased serum luteinizing hormone concentrations ( p = 0.002), and changes in testicular tissue vascularization (lighter and less red testicular parenchyma; p ≤ 0.001), the responses were variable. Sharp decreases in testes index ( p < 0.001), Leydig cell volume density ( p < 0.001), Leydig cell nucleus‐to‐cytoplasm ratio ( p < 0.001), and testosterone concentration ( p < 0.001) were observed in mature immunocastrated boars clustered with young immunocastrated pigs compared with those that clustered with entire males. Additionally, mature immunocastrated boars clustered with young immunocastrated pigs showed lower hydroxysteroid 17‐beta dehydrogenase 7 expression than entire males ( p < 0.05). The young immunocastrated pigs group showed higher follicle‐stimulating hormone receptors than the entire males and mature immunocastrated boars, lower steroidogenic acute regulatory protein expression levels compared with entire males, and mature immunocastrated boars clustered with entire males ( p < 0.01). Conclusion: The two‐dose vaccination regime resulted in progressive but variable regression of testicular function in adult (post‐pubertal) pigs; however, it was insufficient to induce a complete immunocastration response in all animals.